Evaluating the Effectiveness of Virtual Reality Training Systems in Improving Motor Learning and Reaction Time in Team Sports - Sudiadharma, Sudiadharma (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study aims to evaluate the effectiveness of Virtual Reality (VR) training systems in enhancing motor learning and reaction time in team sports. A qualitative research design was employed, utilizing a systematic literature review (SLR) to analyze and synthesize existing studies on the application of VR in sports training. The review focused on peer-reviewed articles, conference proceedings, and other relevant sources to examine the impact of VR on motor skill acquisition and reaction time improvement, particularly in team sports such as football, basketball, and volleyball. The findings suggest that VR training systems significantly enhance motor learning by providing athletes with an immersive, game-like environment that improves cognitive-motor integration and skill retention. Moreover, VR training systems also demonstrated a positive effect on reaction time, with athletes responding faster to stimuli and improving decision-making under pressure. However, while VR training showed substantial benefits, limitations such as the inability to replicate the full complexity of live competition were noted. Additionally, the impact of VR training varied across different team sports, with football and basketball benefiting more due to the fast-paced, dynamic nature of these sports. The study concludes that VR training systems offer valuable tools for enhancing motor skills and reaction time, but further research is needed to refine the technology and integrate it more effectively into traditional training methods.